A Survey of Team Members' Perceptions of Coaching Activities Related to Tier 1 SWPBIS Implementation. (January 2020) - Bastable, Eoin; Massar, Michelle M.; McIntosh, Kent
Coaching is an important component in multi-tiered systems of support (MTSS) such as school-wide positive behavioral interventions and supports (SWPBIS), but little is known about which coaching activities are most related to sustained implementation of this school-wide framework. A survey was developed to examine the amount of receipt and perceived importance of coaching activities delivered to SWPBIS school teams. Respondents included SWPBIS team members ( n = 264) implementing Tier 1 SWPBIS for at least 3 years in 138 districts across nine states. Partial correlations were conducted on a subsample of schools ( n = 131) using the Benchmarks of Quality (BoQ) to assess self-reported implementation fidelity to examine the extent to which each coaching activity was associated with fidelity of implementation of SWPBIS. Results indicated Assisting With Team Action Planning, Assisting With Data Collection, and Sharing Knowledge of SWPBIS Systems were perceived as most important to SWPBIS sustainability. Partial correlations showed two activities were statistically significant and positively correlated with SWPBIS fidelity of implementation: Running Data Reports for the Team and Modeling SWPBIS Implementation. Implications for assessing and differentiating coaching supports delivered to schools are discussed.